Efforts to Scale the e-Extension Solution GeoAgro-MiSR by the Government of Egypt - Attaher, Samar; Govind, Ajit; Atassi, Layal; Devkota Wasti, Mina Kumari; Nangia, Vinay (International Center for Agricultural Research in the Dry Areas, 2025)
The partnership between ICARDA and the Agricultural Research Centre of Egypt is one of the major pillars of the structure of the Egypt use case of the EiA initiative. The goal of this partnership is to support and reinforce agricultural digital extension transformation, aiming to improve the productivity of the agricultural systems and empower the low-resilient smallholder farmers. Accordingly, it focused on the design and development of a digital extension platform that supports the resilience of smallholder farmers with up-to-date recommendations on smart agricultural practices.